Screening of Factors Influencing Dyeing Uptake Exhaustion of Betacyanin Extracted onto Spun Silk using Fractional Factorial Design - Norasiha, Hamid; Mimi Sakinah, A. M.; Mazrul Nizam, Abu Seman (2016)
Dyeing uptake exhaustion of betacyanin extract onto spun silk using batch process was carried out. In order to determine the most influence to the dye uptake percentage, the 25 full factorial design was used. The five factors were examined, namely temperature, dyeing time, dye bath concentration, salt concentration and the initial pH of the solution. Based on the ANOVA, it was verified that dyeing time, dye bath concentration and pH variables had an influence on the maximum dye uptake percentage at the level of 5% probability. The main effect was found to be determined as pH (P<0.001), dye bath (P<0.0001) and dyeing time (P<0.008). Temperature and salt concentration was determined as a secondary effect.